Pengaruh Pihak Ketiga, Biaya Operasional Pendapatan Operasional dan Kredit terhadap Kinerja Keuangan pada Sektor Perbankan di Bursa Efek Indonesia - Noni Irma Hotang; Rupiwita Munte; Serevina Simanjuntak (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The study was conducted to examine Third Party Funds, Operational Costs, Operational Income and Loans Disbursed on Financial Performance in the banking sector listed on the Indonesian Stock Exchange for the period 2015-2017. The sampling system used was saturated sampling. This study obtained a sample of 26 companies and then multiplied by 3 years of the test period, the total number of samples obtained was 78 data, which were analyzed in this study using annual financial reports taken from multiple linear regression research methods, classical assumption test and hypothesis test using the F test and T test using the SPSS program. Which parties to Third Party Funds, Operating Costs Operating Income (BOPO) and Loans Distributed simultaneously have a significant effect on financial performance to banking companies, through this research it could be that Third Party Funds, Operational Income Operational Costs (BOPO) and Loans Disbursed by the variables studied was 2.7% and the remaining 9.3% was presented by other factors, for example: EAR, LAR, NPL, Company Size, DER, Credit Ratio and other variables.